Composite foil and preparation process thereof

By using composite foils in lithium-ion batteries, including polymer layer, base layer, metal layer and protective layer, the problem of large thickness of the adapter is solved, the specific energy of the battery is improved, and the anti-stickness and hydrophobic properties of the material are improved through the preparation of modified fluorosilic resin.

CN119786618AActive Publication Date: 2025-04-08JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411961843.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the existing lithium-ion batteries, the thickness of the adapter is relatively large, which limits the increase in the specific energy of the battery, and the weight reduction effect of the functional current collector intermediate layer is not significant.

Method used

Using composite foils, including polymer layer, base layer, metal layer and protective layer, through specific layer structure and material combination, reduce the thickness of the metal layer and improve the overall mechanical and hydrophobic properties of the material.

Benefits of technology

It realizes the reduction of the thickness of the adapter and the improvement of the battery specific energy. At the same time, the anti-stickness and hydrophobic properties of the composite foil are improved by the preparation of modified fluorosilicone resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a composite foil and a preparation process thereof, and relates to the technical field of lithium ion batteries. The composite foil comprises a polymer layer, a priming layer, a metal layer and a protective layer, a bottom layer is arranged on the upper surface or / and the lower surface of the polymer layer, and the metal layer is arranged on one side, deviating from the polymer layer, of the bottom layer; and the protective layer is arranged on the outer surface of the metal layer. According to the invention, the polymer layer is modified, so that an epoxy group of the multi-component epoxy chain extender and a carboxyl-terminated group of PET are subjected to a ring-opening reaction, the molecular weight of PET is increased, the mechanical strength of PET is improved, and the overall mechanical property of the material is improved; the priming layer is modified fluorosilicone resin, and the resin contains organic fluorine, has strong polarity, is easy to agglomerate when being heated and cured, and forms an aggregate of inorganic hybrid particles wrapped by C-F bonds, so that a resin coating shrinks, bulges are formed, and the coating is endowed with excellent anti-sticking performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, in particular to a composite foil material and a preparation process thereof. Background Art

[0002] As lithium-ion batteries pursue high specific energy, lightweighting has become a research focus. The functional current collector intermediate layer uses polymer materials instead of metals, which reduces the weight by 50%-80% compared to pure metal current collectors, which can increase the specific energy of the battery by 5%-10%. If the functional current collector is to be used in the battery, it is necessary to first perform a transfer welding operation, that is, to weld the transfer body to the functional current collector through an ultrasonic welding machine to achieve circuit conduction. To further improve the specific energy on this basis, it is necessary to reduce the thickness of the transfer body and use thinner metal foil. Summary of the invention

[0003] The object of the present invention is to provide a composite foil material and a preparation process thereof to solve the problems raised in the prior art.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a composite foil material, comprising a polymer layer, a primer layer, a metal layer and a protective layer; the primer layer is arranged on the upper surface or / and the lower surface of the polymer layer, and the metal layer is arranged on the side of the primer layer away from the polymer layer; the protective layer is arranged on the outer surface of the metal layer.

[0005] Further, the polymer layer is one or more of polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyimide, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene and polyamide; The polymer layer has a thickness of 1-8 μm.

[0006] Furthermore, the metal layer material is copper, aluminum, or a mixture of the two; The thickness of the metal layer is 1-3 μm.

[0007] Furthermore, the number of layers of the base layer is 1-2 layers; The thickness of the primer layer is 2-5 μm.

[0008] Furthermore, the protective layer slurry includes inorganic particles and a binder; The inorganic particles are a mixture of one or more of aluminum oxide, tin oxide and silicon nitride; The binder is a polyvinyl alcohol solution; The thickness of the protective layer is 2-4 μm.

[0009] Furthermore, the volume ratio of the inorganic particles to the binder is (7-9): (1-3).

[0010] A preparation process of a composite foil comprises the following steps: Take the polymer layer, apply a primer slurry evenly on the upper surface and / or lower surface of the polymer layer, set the metal layer on the side of the primer slurry away from the polymer layer, dry it to form a primer layer, and then spray a protective layer slurry on the outer surface of the metal layer, dry it to form a protective layer, and obtain a composite foil.

[0011] Furthermore, the drying process conditions are: temperature 80-120°C, time 3-5min.

[0012] Furthermore, the process conditions of spraying are: feeding rate 10-20g / min.

[0013] Furthermore, the polymer layer is modified PET, and the specific preparation process is as follows: PET, chain extender and polyester elastomer are blended and melt-extruded to obtain modified PET, which is then pulled and shaped to form a polymer layer.

[0014] Furthermore, the mass ratio of PET, chain extender, and polyester elastomer is 100:(0.2-0.6):(2-7).

[0015] Furthermore, the process conditions of melt extrusion are: temperature 170-210° C., rotation speed 80-100 r / min.

[0016] Further, the chain extender is ADR-4400, which can be purchased from Shanghai Kaiyin Chemical Co., Ltd.; Polyester elastomer: brand G5544, can be purchased from Suzhou Lawrence Plastics Co., Ltd.; PET: Brand number RE5329, can be purchased from Dongguan Xinshengli Plastic New Material Technology Co., Ltd.

[0017] In the above technical scheme, the chain extender is a polycyclic epoxy chain extender, the epoxy group of which can undergo a ring-opening reaction with the terminal carboxyl group of PET, thereby increasing the molecular weight of PET and improving the mechanical strength of PET. The chain extender can also improve the dispersibility of PET molecules during processing, reduce degradation, and enhance the overall mechanical properties of the material. The blending of polyester elastomer and PET can improve the overall toughness of the material. When subjected to impact load, the elastomer particles dispersed in the PET matrix absorb part of the impact energy through elastic deformation, thereby reducing the impact energy on the PET matrix. The polyester elastomer has good compatibility with PET, and no additional compatibilizer is required to achieve effective fusion of the two phases.

[0018] Furthermore, the primer layer is a modified fluorosilicone resin, and the specific preparation process is as follows: Step (1): trifluoropropyltrimethylcyclotrisiloxane and hexamethylcyclotrisiloxane are mixed, the temperature is raised to 35-45°C, concentrated sulfuric acid is added, the reaction is carried out for 0.5-1h, and then tetramethyldihydrodisiloxane is added, the reaction is carried out for 3-5h, the pH is adjusted to neutral, and the mixture is filtered to obtain fluorine-containing and hydrogen-containing silicone oil; Step (2): Mix the fluorine-containing hydrogen-containing silicone oil obtained in step (1) with vinyl triethoxysilane, heat and stir to react, add chloroplatinic acid, and react at a constant temperature for 2-4 hours to obtain an alkoxy-modified fluorine-containing hydrogen-containing silicone oil; Step (3): Mix the alkoxy-modified fluorine-containing hydrogen-containing silicone oil obtained in step (2) with ethyl orthosilicate, octyltriethoxysilane and anhydrous ethanol, adjust the pH to 3-4, heat the reaction, slowly add distilled water, and react for 5-6 hours to obtain a modified fluorosilicone resin.

[0019] Furthermore, in step (1), the mass ratio of trifluoropropyltrimethylcyclotrisiloxane, hexamethylcyclotrisiloxane, concentrated sulfuric acid, and tetramethyldihydrogendisiloxane is (1-3): (1-5): (0.1-0.2): (2-4).

[0020] Furthermore, in step (1), trifluoropropyltrimethylcyclotrisiloxane: CAS No. 2374-14-3 can be purchased from Jiangsu Pules Biotechnology Co., Ltd.; Hexamethylcyclotrisiloxane: CAS No. 541-05-9, available from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; Concentrated sulfuric acid: CAS No. 7664-93-9, available from Nanjing Shengqinghe Chemical Co., Ltd.; Tetramethyldihydrogendisiloxane: CAS No. 3277-26-7, can be purchased from Wuhan Chengtian Fine Chemical Co., Ltd.

[0021] Furthermore, in step (2), the mass ratio of fluorine-containing hydrogen-containing silicone oil, vinyl triethoxysilane, and chloroplatinic acid is (0.9-1.1):1:(0.001-0.003).

[0022] Furthermore, the process conditions for the heating and stirring reaction in step (2) are: temperature 70-80°C, time 10-20min, and rotation speed 30-40r / min.

[0023] Furthermore, in step (2), vinyl triethoxysilane: CAS No. 1067-53-4, can be purchased from Shandong Huachen New Materials Co., Ltd.; Chloroplatinic acid: CAS No. 16941-12-1, can be purchased from Nantong Runfeng Petrochemical Co., Ltd.

[0024] Furthermore, in step (3), the molar ratio of alkoxy-modified fluorine-containing hydrogen-containing silicone oil, ethyl orthosilicate, octyltriethoxysilane, and anhydrous ethanol is (4-6): (2-4): (1-3): (3-5).

[0025] Furthermore, the process conditions for the temperature-raising reaction in step (3) are: temperature 40-50° C., time 20-30 min.

[0026] Furthermore, in step (3), the speed of adding distilled water is 3-5 s / drop.

[0027] Furthermore, in step (3), ethyl orthosilicate: CAS No. 78-10-4, can be purchased from Shandong Yuanjin New Materials Co., Ltd.; Octyltriethoxysilane: CAS No. 2943-75-1, available from Guangzhou Zhongjie New Materials Co., Ltd.; Anhydrous ethanol: CAS No. 64-17-5, can be purchased from Merck Reagents.

[0028] In the above technical scheme, trifluoropropyl trimethylcyclotrisiloxane, hexamethylcyclotrisiloxane and tetramethyl dihydrogen disiloxane are used as raw materials, and a ring-opening polycondensation reaction is carried out under the action of an acid catalyst. The silicon-oxygen bond in trifluoropropyl trimethylcyclotrisiloxane is broken to form a linear siloxane chain, and the terminal hydrogen group of tetramethyl dihydrogen disiloxane participates in the chain growth as a capping agent to generate a fluorine-containing hydrogen-containing silicone oil; the silicon-hydrogen bond in the fluorine-containing hydrogen-containing silicone oil has high activity, and undergoes a silylation reaction with the vinyl group of vinyl triethoxysilane to form a silicon-carbon bond under the catalytic action of chloroplatinic acid, and an ethoxy group is also introduced to generate an alkoxy-modified fluorine-containing hydrogen-containing silicone oil; ethyl orthosilicate and octyl triethoxysilane undergo a hydrolysis reaction to generate a silanol bond, and the alkoxy-modified fluorine-containing hydrogen-containing silicone oil The alkoxy groups in the resin participate in the hydrolysis to generate fluorine-containing and hydrogen-containing silanols, and the generated silanols undergo condensation reactions and dehydrate to form silicon-oxygen bonds, thereby constructing a network structure of the silicone resin and obtaining a modified fluorosilicone resin. The resin contains organic fluorine and has strong polarity. Ethyl orthosilicate undergoes hydrolysis and condensation to generate silicon dioxide nanoparticles, which are easily agglomerated when cured by heat to form agglomerates of inorganic hybrid particles wrapped by CF bonds, thereby causing the resin coating to shrink and form protrusions, giving the coating excellent anti-sticking properties. In addition, the fluorine-containing group has a strong polarity and migrates to the surface of the coating when heated. Under the joint action of organic and inorganic, the surface energy of the coating is reduced. In addition, the long-chain alkyl group in octyltriethoxysilane has good hydrophobicity, which further improves the hydrophobicity of the coating.

[0029] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. The epoxy group of the polycyclic epoxy chain extender can undergo a ring-opening reaction with the terminal carboxyl group of PET, thereby increasing the molecular weight of PET and improving the mechanical strength of PET. The chain extender can also improve the dispersibility of PET molecules during processing, reduce degradation, and enhance the overall mechanical properties of the material. The blending of polyester elastomer and PET can improve the overall toughness of the material. When subjected to impact loads, the elastomer particles dispersed in the PET matrix absorb part of the impact energy through elastic deformation, which can reduce the impact energy on the PET matrix. The polyester elastomer has good compatibility with PET, and no additional compatibilizer is required to achieve effective fusion of the two phases.

[0030] 2. Using trifluoropropyltrimethylcyclotrisiloxane, hexamethylcyclotrisiloxane and tetramethyldihydrodisiloxane as raw materials, modified fluorosilicone resin is prepared through ring-opening polycondensation, hydrosilylation and polycondensation reaction. The resin contains organic fluorine and has strong polarity. Ethyl orthosilicate is hydrolyzed and polycondensed to generate silicon dioxide nanoparticles, which are easy to agglomerate when cured by heat to form agglomerates of inorganic hybrid particles wrapped by CF bonds, thereby causing the resin coating to shrink and form protrusions, giving the coating excellent anti-sticking properties. In addition, the fluorine-containing group has a strong polarity and migrates to the surface of the coating when heated. Under the joint action of organic and inorganic groups, the surface energy of the coating is reduced and the hydrophobic property is improved. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the following specific implementations, Trifluoropropyltrimethylcyclotrisiloxane: CAS No. 2374-14-3, available from Jiangsu Pules Biotechnology Co., Ltd.; Hexamethylcyclotrisiloxane: CAS No. 541-05-9, available from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; Concentrated sulfuric acid: CAS No. 7664-93-9, available from Nanjing Shengqinghe Chemical Co., Ltd.; Tetramethyldihydrogendisiloxane: CAS No. 3277-26-7, available from Wuhan Chengtian Fine Chemical Co., Ltd.; Vinyl triethoxysilane: CAS No. 1067-53-4, available from Shandong Huachen New Materials Co., Ltd.; Chloroplatinic acid: CAS No. 16941-12-1, can be purchased from Nantong Runfeng Petrochemical Co., Ltd.; Ethyl orthosilicate: CAS No. 78-10-4, can be purchased from Shandong Yuanjin New Materials Co., Ltd.; Octyltriethoxysilane: CAS No. 2943-75-1, available from Guangzhou Zhongjie New Materials Co., Ltd.; Anhydrous ethanol: CAS No. 64-17-5, can be purchased from Merck Reagent; The chain extender is ADR-4400, which can be purchased from Shanghai Kaiyin Chemical Co., Ltd.; Polyester elastomer: brand G5544, can be purchased from Suzhou Lawrence Plastics Co., Ltd.; PET: brand name RE5329, can be purchased from Dongguan Xinshengli Plastic New Material Technology Co., Ltd.; Prepare protective layer slurry: mix inorganic particles with a binder with a concentration of 10%, stir evenly, add polyvinyl alcohol, adjust the solid content to 50%, and stir evenly; The inorganic particles are aluminum oxide, CAS No. 1344-28-1, which can be purchased from Yangzhou Zhongtianli New Materials Co., Ltd. The binder is a polyvinyl alcohol solution: CAS No. 14-55-63, which can be purchased from Shandong Shoucheng Chemical Co., Ltd.

[0033] Embodiment 1: A process for preparing a composite foil comprises the following steps: 1. Preparation of polymer layer: PET, chain extender and polyester elastomer are blended and melt extruded to obtain modified PET, which is then pulled and shaped to form a polymer layer; the mass ratio of PET, chain extender and polyester elastomer is 100:0.2:2; the process conditions of melt extrusion are: temperature 170°C, rotation speed 80r / min; the polymer layer thickness is 1μm; 2. Preparation of modified fluorosilicone resin: Step (1): Mix trifluoropropyl trimethylcyclotrisiloxane and hexamethylcyclotrisiloxane, heat to 35°C, add concentrated sulfuric acid, react for 0.5h, then add tetramethyldihydrogendisiloxane, react for 3h, adjust the pH to neutral, filter, and obtain fluorine-containing hydrogen silicone oil; Step (2): Mix the fluorine-containing hydrogen silicone oil obtained in step (1) with vinyl triethoxysilane, heat and stir to react, add chloroplatinic acid, and react at constant temperature for 2h to obtain alkoxy-modified fluorine-containing hydrogen silicone oil; Step (3): Mix the alkoxy-modified fluorine-containing hydrogen silicone oil obtained in step (2) with ethyl orthosilicate, octyl triethoxysilane and anhydrous ethanol, adjust the pH to 3, heat to react, slowly add distilled water, and react for 5h to obtain modified fluorine silicone resin fat; in step (1), the mass ratio of trifluoropropyl trimethyl cyclotrisiloxane, hexamethyl cyclotrisiloxane, concentrated sulfuric acid, and tetramethyl dihydrogen disiloxane is 1:1:0.1:2; in step (2), the mass ratio of fluorine-containing hydrogen silicone oil, vinyl triethoxysilane, and chloroplatinic acid is 0.9:1:0.001; the process conditions for heating and stirring the reaction in step (2) are: temperature 70°C, time 10 min, and speed 30 r / min; in step (3), the molar ratio of alkoxy-modified fluorine-containing hydrogen silicone oil, ethyl orthosilicate, octyl triethoxysilane, and anhydrous ethanol is 4:2:1:3; the process conditions for the temperature reaction in step (3) are: temperature 40°C, time 20 min; the speed of adding distilled water in step (3) is 3s / drop; 3. Preparation of composite foil: Take the polymer layer, apply the primer slurry evenly on the upper surface and / or the lower surface of the polymer layer, arrange the metal layer on the side of the primer slurry away from the polymer layer, dry it to form a primer layer, and then spray the protective layer slurry on the outer surface of the metal layer, dry it to form a protective layer, and obtain a composite foil; the drying process conditions are: temperature 80°C, time 3min; primer layer thickness 2μm; metal layer thickness 1μm; spraying process conditions are: feed rate 10g / min; protective layer thickness 2μm; protective layer slurry includes inorganic particles and binder; the volume ratio of inorganic particles to binder is 7:3.

[0034] Embodiment 2: A process for preparing a composite foil comprises the following steps: 1. Preparation of polymer layer: PET, chain extender and polyester elastomer are blended and melt extruded to obtain modified PET, which is then pulled and shaped to form a polymer layer; the mass ratio of PET, chain extender and polyester elastomer is 100:0.4:5; the process conditions of melt extrusion are: temperature 190°C, rotation speed 90r / min; the polymer layer thickness is 4μm; 2. Preparation of modified fluorosilicone resin: Step (1): trifluoropropyl trimethylcyclotrisiloxane and hexamethylcyclotrisiloxane are mixed, the temperature is raised to 40°C, concentrated sulfuric acid is added, the reaction is carried out for 0.7h, and then tetramethyl dihydrogen disiloxane is added, the reaction is carried out for 4h, the pH is adjusted to neutral, and filtered to obtain fluorine-containing hydrogen-containing silicone oil; Step (2): the fluorine-containing hydrogen-containing silicone oil obtained in step (1) is mixed with vinyl triethoxysilane, heated and stirred for reaction, chloroplatinic acid is added, and the reaction is carried out at a constant temperature for 3h to obtain alkoxy-modified fluorine-containing hydrogen-containing silicone oil; Step (3): the alkoxy-modified fluorine-containing hydrogen-containing silicone oil obtained in step (2) is mixed with ethyl orthosilicate, octyl triethoxysilane and anhydrous ethanol, the pH is adjusted to 3, the temperature is raised for reaction, distilled water is slowly added dropwise, and the reaction is carried out for 5.5h to obtain modified fluorine-containing hydrogen-containing silicone oil. Silicone resin; in step (1), the mass ratio of trifluoropropyl trimethyl cyclotrisiloxane, hexamethyl cyclotrisiloxane, concentrated sulfuric acid, and tetramethyl dihydrogen disiloxane is 2:3:0.1:3; in step (2), the mass ratio of fluorine-containing hydrogen-containing silicone oil, vinyl triethoxysilane, and chloroplatinic acid is 1:1:0.002; the process conditions for the heating and stirring reaction in step (2) are: temperature 75°C, time 15 min, and speed 35 r / min; in step (3), the molar ratio of alkoxy-modified fluorine-containing hydrogen-containing silicone oil, ethyl orthosilicate, octyl triethoxysilane, and anhydrous ethanol is 5:3:2:4; the process conditions for the temperature reaction in step (3) are: temperature 45°C, time 25 min; the speed of adding distilled water in step (3) is 4s / drop; 3. Preparation of composite foil: Take the polymer layer, apply the primer slurry evenly on the upper surface and / or the lower surface of the polymer layer, arrange the metal layer on the side of the primer slurry away from the polymer layer, dry it to form a primer layer, and then spray the protective layer slurry on the outer surface of the metal layer, dry it to form a protective layer, and obtain a composite foil; the drying process conditions are: temperature 100°C, time 4min; primer layer thickness 4μm; metal layer thickness 2μm; spraying process conditions are: feed rate 15g / min; protective layer thickness 3μm; protective layer slurry includes inorganic particles and binder; the volume ratio of inorganic particles to binder is 8:2.

[0035] Embodiment 3: A process for preparing a composite foil comprises the following steps: 1. Preparation of polymer layer: PET, chain extender and polyester elastomer are blended and melt extruded to obtain modified PET, which is then pulled and shaped to form a polymer layer; the mass ratio of PET, chain extender and polyester elastomer is 100:0.6:7; the process conditions of melt extrusion are: temperature 210°C, rotation speed 100r / min; the polymer layer thickness is 8μm; 2. Preparation of modified fluorosilicone resin: Step (1): Mix trifluoropropyl trimethylcyclotrisiloxane and hexamethylcyclotrisiloxane, heat to 45°C, add concentrated sulfuric acid, react for 1 hour, then add tetramethyldihydrogendisiloxane, react for 5 hours, adjust the pH to neutral, filter, and obtain fluorine-containing hydrogen silicone oil; Step (2): Mix the fluorine-containing hydrogen silicone oil obtained in step (1) with vinyl triethoxysilane, heat and stir to react, add chloroplatinic acid, and react at a constant temperature for 4 hours to obtain alkoxy-modified fluorine-containing hydrogen silicone oil; Step (3): Mix the alkoxy-modified fluorine-containing hydrogen silicone oil obtained in step (2) with ethyl orthosilicate, octyl triethoxysilane and anhydrous ethanol, adjust the pH to 4, heat to react, slowly add distilled water, and react for 6 hours to obtain modified fluorosilicone resin ; In step (1), the mass ratio of trifluoropropyl trimethyl cyclotrisiloxane, hexamethyl cyclotrisiloxane, concentrated sulfuric acid, and tetramethyl dihydrogen disiloxane is 3:5:0.2:4; in step (2), the mass ratio of fluorine-containing hydrogen silicone oil, vinyl triethoxysilane, and chloroplatinic acid is 1.1:1:0.003; the process conditions for the heating and stirring reaction in step (2) are: temperature 80°C, time 20 min, and speed 40 r / min; in step (3), the molar ratio of alkoxy-modified fluorine-containing hydrogen silicone oil, ethyl orthosilicate, octyl triethoxysilane, and anhydrous ethanol is 6:4:3:5; the process conditions for the temperature reaction in step (3) are: temperature 50°C, time 30 min; the speed of adding distilled water in step (3) is 5s / drop; 3. Preparation of composite foil: Take the polymer layer, apply the primer slurry evenly on the upper surface and / or the lower surface of the polymer layer, arrange the metal layer on the side of the primer slurry away from the polymer layer, dry it to form a primer layer, and then spray the protective layer slurry on the outer surface of the metal layer, dry it to form a protective layer, and obtain a composite foil; the drying process conditions are: temperature 120℃, time 5min; primer layer thickness 5μm; metal layer thickness 3μm; spraying process conditions are: feed rate 20g / min; protective layer thickness 4μm; protective layer slurry includes inorganic particles and binder; the volume ratio of inorganic particles to binder is 9:1.

[0036] Comparative Example 1: Using Example 1 as a comparison, PET is not modified, and other process conditions remain unchanged. The specific process is as follows: 1. Preparation of modified fluorosilicone resin: Step (1): Mix trifluoropropyl trimethylcyclotrisiloxane and hexamethylcyclotrisiloxane, heat to 35°C, add concentrated sulfuric acid, react for 0.5h, then add tetramethyldihydrogendisiloxane, react for 3h, adjust the pH to neutral, filter, and obtain fluorine-containing hydrogen silicone oil; Step (2): Mix the fluorine-containing hydrogen silicone oil obtained in step (1) with vinyl triethoxysilane, heat and stir to react, add chloroplatinic acid, and react at constant temperature for 2h to obtain alkoxy-modified fluorine-containing hydrogen silicone oil; Step (3): Mix the alkoxy-modified fluorine-containing hydrogen silicone oil obtained in step (2) with ethyl orthosilicate, octyl triethoxysilane and anhydrous ethanol, adjust the pH to 3, heat to react, slowly add distilled water, and react for 5h to obtain modified fluorine silicone resin fat; in step (1), the mass ratio of trifluoropropyl trimethyl cyclotrisiloxane, hexamethyl cyclotrisiloxane, concentrated sulfuric acid, and tetramethyl dihydrogen disiloxane is 1:1:0.1:2; in step (2), the mass ratio of fluorine-containing hydrogen silicone oil, vinyl triethoxysilane, and chloroplatinic acid is 0.9:1:0.001; the process conditions for heating and stirring the reaction in step (2) are: temperature 70°C, time 10 min, and speed 30 r / min; in step (3), the molar ratio of alkoxy-modified fluorine-containing hydrogen silicone oil, ethyl orthosilicate, octyl triethoxysilane, and anhydrous ethanol is 4:2:1:3; the process conditions for the temperature reaction in step (3) are: temperature 40°C, time 20 min; the speed of adding distilled water in step (3) is 3s / drop; 2. Preparation of composite foil: Take the polymer layer, apply the primer slurry evenly on the upper surface and / or the lower surface of the polymer layer, arrange the metal layer on the side of the primer slurry away from the polymer layer, dry it to form the primer layer, and then spray the protective layer slurry on the outer surface of the metal layer, dry it to form a protective layer, and obtain a composite foil; the drying process conditions are: temperature 80°C, time 3min; PET base layer thickness is 1μm; primer layer thickness is 2μm; metal layer thickness is 1μm; spraying process conditions are: feed rate 10g / min; protective layer thickness is 2μm; the protective layer slurry includes inorganic particles and binder; the volume ratio of inorganic particles to binder is 7:3.

[0037] Comparative Example 2: Compared with Example 1, the base layer was replaced with ordinary fluorosilicone resin, and the other process conditions remained unchanged.

[0038] Comparative Example 3: Using Example 1 as a comparison, the base layer was replaced with a polyurethane adhesive, and the other conditions remained unchanged.

[0039] Experiment: The composite foils obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were taken and their properties were tested; Expansion and contraction performance test: The composite foil is made into a sample with a length of 15 cm and a width of 2 cm. One end is welded with a pole ear, sealed and immersed in an electrolyte (LiPF6) for 24 hours, and then placed in an oven for baking at 50℃, 100℃, 150℃, 200℃, 220℃, and 250℃ for 30 minutes. The degree of pulling of the metal layer after the composite foil base film shrinks is observed, and whether the metal layer has cracks, and its expansion coefficient and contraction rate are measured; Peel strength test: Take the prepared sample and perform a peel strength test according to GB / T 2792-2014; Tensile strength: Take the prepared sample and test it according to GB / T13022-1991; Table 1 Test results of expansion coefficient and thermal shrinkage rate of composite foil in Example 1

[0040] Table 2 Test results of expansion coefficient and thermal shrinkage rate of composite foil in Example 2

[0041] Table 3 Test results of expansion coefficient and thermal shrinkage rate of composite foil in Example 3

[0042] Table 4 Test results of expansion coefficient and thermal shrinkage rate of composite foil in comparative example 1

[0043] Table 5 Test results of expansion coefficient and thermal shrinkage rate of composite foil in comparative example 2

[0044] Table 6 Test results of expansion coefficient and thermal shrinkage rate of composite foil in comparative example 3

[0045] Table 7 Composite foil peel strength and tensile strength test results

[0046] The following conclusions can be drawn from Tables 1-6: when the test temperature is 50°C, the polymer layer does not expand or shrink; when the test temperature is 100°C, the polymer layer undergoes thermal expansion and basically does not shrink; when the test temperature is 150°C, the expansion coefficient of the polymer layer decreases and basically does not shrink; when the test temperature is 200-250°C, the polymer layer begins to shrink, and the shrinkage rate increases with increasing temperature.

[0047] The following conclusions can be drawn from Table 7: The composite foils in Examples 1-3 have lower peel strength than the composite foils in Comparative Examples 1-3. When the temperature begins to rise, the polymer layer begins to expand and is more easily separated from the metal layer. The polymer layer has a higher tensile strength and is not easily broken by itself, so it has a higher safety factor. This fully demonstrates that the setting of the material of the product produced by the present invention can promote the improvement of the tensile strength of the composite foil and the reduction of the peel strength.

[0048] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A composite foil, characterized in that: It comprises a polymer layer, a primer layer, a metal layer and a protective layer; the primer layer is arranged on the upper surface or / and the lower surface of the polymer layer, the metal layer is arranged on the side of the primer layer away from the polymer layer; the protective layer is arranged on the outer surface of the metal layer.

2. A composite foil material according to claim 1, characterized in that: The polymer layer is a mixture of one or more of polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyimide, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene and polyamide.

3. A composite foil according to claim 1, characterized in that: The metal layer is made of copper or aluminum.

4. The composite foil according to claim 1, characterized in that: The number of layers of the base layer is 1-2 layers.

5. A process for preparing a composite foil, characterized in that: The following steps are involved: Take the polymer layer, apply a primer slurry evenly on the upper surface and / or lower surface of the polymer layer, set the metal layer on the side of the primer slurry away from the polymer layer, dry it to form a primer layer, and then spray a protective layer slurry on the outer surface of the metal layer, dry it to form a protective layer, and obtain a composite foil.

6. The process for preparing a composite foil according to claim 5, characterized in that: The specific preparation process of the polymer layer is as follows: PET, chain extender and polyester elastomer are blended, melt-extruded, pulled and shaped to form a polymer layer.

7. The process for preparing a composite foil according to claim 5, characterized in that: The bottom layer is a modified silicone fluorine resin, and the specific preparation process is as follows: Step (1): trifluoropropyltrimethylcyclotrisiloxane and hexamethylcyclotrisiloxane are mixed, the temperature is raised to 35-45° C., concentrated sulfuric acid is added, the reaction is carried out for 0.5-1 h, and then tetramethyldihydrodisiloxane is added, the reaction is carried out for 3-5 h, the pH is adjusted to neutral, and the mixture is filtered to obtain fluorine-containing and hydrogen-containing silicone oil; Step (2): mixing the fluorine-containing hydrogen-containing silicone oil obtained in step (1) with vinyl triethoxysilane, heating and stirring to react, adding chloroplatinic acid, and reacting at a constant temperature for 2-4 hours to obtain an alkoxy-modified fluorine-containing hydrogen-containing silicone oil; Step (3): Mix the alkoxy-modified fluorine-containing hydrogen-containing silicone oil obtained in step (2) with ethyl orthosilicate, octyltriethoxysilane and anhydrous ethanol, adjust the pH to 3-4, heat the reaction, slowly add distilled water, and react for 5-6 hours to obtain a modified silicone fluorine resin.

8. The process for preparing a composite foil according to claim 6, characterized in that: The mass ratio of PET, chain extender and polyester elastomer is 100:(0.2-0.6):(2-7).

9. The process for preparing a composite foil according to claim 7, characterized in that: In step (1), the mass ratio of trifluoropropyltrimethylcyclotrisiloxane, hexamethylcyclotrisiloxane, concentrated sulfuric acid and tetramethyldihydrogendisiloxane is (1-3): (1-5): (0.1-0.2): (2-4).

10. The process for preparing a composite foil according to claim 7, characterized in that: In step (2), the mass ratio of fluorine-containing and hydrogen-containing silicone oil, vinyl triethoxysilane and chloroplatinic acid is (0.9-1.1):1:(0.001-0.003).

Citation Information

Patent Citations

  • Process for preparing non-sticky, cross-linked organopolysiloxane composition-based particules by polycondensation reactions

    CA2007879A1

  • Silicone oil microcapsule with slow-release characteristics and preparation method thereof

    CN102030990A

  • Battery cathode material and preparation method of cathode plate applying same

    CN107170987A

  • Vinyl siloxane grafted hydrogen-containing silicone oil and preparation method thereof

    CN110183666A

  • Porous composite foil, positive pole piece, negative pole piece, semi-solid lithium ion battery and preparation method

    CN115832195A